Analysis of bacterial colonization in humidifying cups used in oxygen therapy in patients admitted to a University Hospital (Research, Society and Development, 2021)
Objectives: To evaluate the microbiological safety of water in the humidifying cups of patients using oxygen therapy and admitted to a University Hospital in the Vale do Submédio do São Francisco. Methods: This is a clinical, longitudinal, observational study involving microbiological analysis of water from humidifiers used in oxygen therapy. The data were collected daily, during a period of six months and analyzed by the Clinical Analysis Laboratory of the University Hospital. For microbiological analysis, the material was incubated at 37 ° C for 48 hours in tubes containing 5mL of Brain-Heart Infusion (BHI), then seeded on Blood Agar. They were considered contaminated as obtaining that bacterial growth. To identify bacterial species and the antibiogram, the BD Phoenix ™ 100 system was used. Results: 52 patients were considered, totaling 279 during the study period, these, 20 (7.16%) bacterial contamination. The most incident pathogens were: A. baumannii, E. cloacae, K. pneumoniae, S. epidermidis. Conclusion: The data accept the adoption of safer rules in the use of oxygen therapy humidifiers. In addition, knowledge of the resistance profile of bacteria allows more effective drug therapy, preventing therapeutic failures.